An easyguide to APA style - Schwartz, Beth M.; Landrum, R. Eric.; Gurung, Regan A. R. (Los Angeles SAGE Publications, 2014)
"Master APA style and format quickly and easily! Written by experienced psychology instructors who are respected members of the APA's Teaching of Psychology division, this guide provides an easy alternative for anyone struggling with APA style. Written in a clear, conversational, and humorous style, this book presents easy-to-understand explanations of how to write research papers, cite research, and do any work requiring APA format. The authors simplify the process with easy-to-follow advice, tips, and visual representations of how to use APA style. This updated edition includes easy-to-read screen shots as well as guidance on where to find answers to commonly asked student questions."--Publisher's website.
"Second edition"--Back cover.
Keywords: Psychology -- Authorship -- Style manuals; Social sciences -- Authorship -- Style manuals; Writing -- standards; Language; Psychology